Pemanfaatan Habitat oleh Monyet Ekor Panjang (Macaca fascicularis) di Taman Nasional Gunung Palung sebagai Sumber Belajar Biologi - Yoga Febriyanda; Ari Sunandar; Anandita Eka Setiadi (Jurnal Penelitian Pendidikan IPA, 2022)
One of the most distributed primate species in Gunung Palung National Park is the long-tailed monkey (Macaca fascicularis). This study aims to determine habitat characteristics, daily activities, use of habitat as a source of food by long-tailed monkeys, and potential use of habitat by long-tailed monkeys in Gunung Palung National Park as a source of learning biology. The study was conducted using the observation method with focal animal sampling data collection techniques in two transects. The results show that the habitat characteristics have a position that is not far from the watershed (watershed) and belongs to the alluvial forest area. The vegetation condition is dominated by trees from the Angiospermae sub-division which is divided into 12 families. The result of the frequency of resting activity is the highest daily activity among the 4 types of activity observed, which is 48 times. While the plant species that became the highest source of diet trees was Blumeodendron tokbrai, with a percentage of 55.56%. Judging from the results of 7 respondents who came from high school teachers in North Kayong Regency, Gunung Palung National Park was suitable as a learning resource. The requirements of learning resources, namely clarity of potential, conformity with learning objectives, the accuracy of targets, clarity of exploration guidelines, and clarity of expected gains, the results of the study on Habitat Utilization by Long-Tailed Monkeys in Gunung Palung National Park in achieving basic competencies in the spatial material scope of biology, various levels of biodiversity, plants, and materials ecology can be used as a learning resource for high school biology class X